Dilema Diplomatik Indonesia: Normalisasi Israel dan Aksesi OECD dalam Two-Level Games - Izzurrahman, Muhammad Hasan; Prayetno, Prayetno (UIR Press, 2025)
Indonesia faces a complex diplomatic dilemma between its commitment to Palestine and demands to normalize relations with Israel as a condition for joining the OECD. This study uses Robert Putnam's Two-Level Games theory to analyze how Indonesia balances pro-Palestinian domestic interests with international demands regarding relations with Israel. The approach used is qualitative with a literature study, where data is collected through scientific articles, official reports, and related news. The data analysis process is carried out using a three-stage coding technique, namely open coding, axial coding, and selective coding, to identify the main themes and build categories relevant to Indonesia's diplomatic dilemma. The findings show that at level I, Indonesia faces pressure to normalize relations with Israel as a condition for accession to the OECD. Meanwhile, at level II, Indonesia must manage domestic interests that strongly support Palestine, while considering the impact on domestic political stability. Nevertheless, Indonesia maintains its principled position on Palestine, despite the significant opportunities that accession to the OECD could bring in terms of boosting Indonesia's economy, increased investment, and global influence.